Estudo das propriedades fotoluminescentes do ZnS e ZnS: Eu obtidos pelo método solvotérmico assistido por microondas - Ferrer, Mateus Meneghetti (Universidade Federal de São Carlos, 2012)
This paper is about the synthesis, characterization and studies of nanostructures of ZnS and ZnS:Eu3+ prepared by microwave-assisted solvothermal method. The influence of the synthesis time in the microwave on the samples of ZnS was investigated in order to have the most proper sample for doping. Therefore, different concentrations of Europium (dopante) were added to the chosen sample. The characterizations of the samples was made by X-ray diffraction, Ultraviolet visible spectroscopy, scanning electron microscopy, transmission electron microscopy and photoluminescence spectroscopy. The method used to the synthesis of ZnS is very efficient because it synthesizes the nanocrystals in shor time and in a low temperature. The study of the X-ray diffraction, Ultraviolet-visible spectroscopy, photoluminescence and transmission electron microscopy showed structural changes in the samples due to the low processing time and the percentage of europium added to the system. The results indicated an increase of the organization with the increase of the time of synthesis. and a disorganization when the europium is added. These structural differences were responsible for the modifications of the photoluminescence profile of the materials due to the different intermediate states. More specifically, in the synthesis of pure ZnS, the organization of the structure with the increase of the time of synthesis was responsible for a photoluminescence band with a higher contribution of the blue region. However, the disorganization due to the addition of Eu3+ resulted in a photoluminescence band with a higher contribution in the orange region.
Keywords: Físico-química; Sulfeto de zinco; Semicondutores; Nanocristais; Fotoluminescência; CIENCIAS EXATAS E DA TERRA::QUIMICA